Primary aortoduodenal fistula with a history of distal gastrectomy. Issue 1 (9th June 2016) - Inoue, Kentaro; Fukunaga, Ryota; Matsubara, Yutaka; Aoyagi, Yukihiko; Matsuda, Daisuke; Kyuragi, Ryoichi; Morisaki, Koichi; Matsumoto, Takuya; Oki, Eiji; Maehara, Yoshihiko
Abstract : Case: A 69‐year‐old man was transferred to our hospital because of an aortoduodenal fistula with hematemesis and pre‐shock vital signs. He had a history of alcoholism, malnutrition, and distal gastrectomy and Billroth I reconstruction. Endovascular aneurysm repair was successfully carried out; however, the presence of comorbidities affected further radical treatment. Outcome: The patient survived for 2 months postoperatively. Conclusion: Endovascular aneurysm repair is a useful first‐line treatment for high‐risk aortoduodenal fistula patients; however, it requires improvement for long‐term outcomes in complicated high‐risk cases.